Introduction to Computer Graphics Using Java 2D and 3D - Klawonn, Frank; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2012)
A basic understanding of the key techniques in computer graphics can open the door to this exciting field and its many applications. This easy-to-follow textbook/reference introduces the fundamental concepts of computer graphics, integrating both technical background and theory with practical examples and applications throughout. Thoroughly revised and updated, this new edition continues to present a user-friendly approach to creating images and animations, complementing the expanded coverage of topics with extensive usage of example programs and exercises. Topics and features: Provides an ideal, self-contained introduction to computer graphics, with theory and practice presented in integrated combination Presents a practical guide to basic computer graphics programming using Java 2D and 3D Includes new and expanded content on the integration of text in 3D, particle systems, billboard behaviours, dynamic surfaces, the concept of level of detail, and the use of functions of two variables for surface modelling Contains many pedagogical tools, including numerous easy-to-understand example programs and end-of-chapter exercises Supplies useful supplementary material, including additional exercises, solutions, and program examples, at the associated website http://public.ostfalia.de/~klawonn/computergraphics This reader-friendly textbook is an essential tool for second-year undergraduate students and above, providing clear and concise explanations of the basic concepts of computer graphics, and enabling the reader to immediately implement these concepts in Java 2D and/or 3D with only elementary knowledge of the programming language.
Introduction -- Basic Principles of Two-Dimensional Graphics -- Drawing Lines and Curves -- Areas, Text and Colours -- Basic Principles of Three-Dimensional Graphics -- Modelling Three-Dimensional Objects -- Visible Surface Determination -- Illumination and Shading -- Special Effects and Virtual Reality -- Useful Links -- Example Programs -- References to Java 2D Classes and Methods -- References to Java 3D Classes and Methods.
Keywords: Computer science; Computer vision; Computer graphics; Computer Science; Computer Graphics; Computer Imaging, Vision, Pattern Recognition and Graphics